Evaluation of the Shore A Hardness of Silicone for Facial Prosthesis as to the Effect of Storage Period and Chemical Disinfection - Guiotti, Aimée Maria [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP] (Lippincott Williams & Wilkins, 2010)
The failure of facial prostheses is caused by limitations in the properties of existing materials, especially flexibility and durability. Therefore, this study evaluated the Shore A hardness of silicone used for fabrication of facial prostheses, Silastic MDX4-4210, according to the influence of storage period, daily disinfection, and 2 types of pigmentation. Thirty specimens were fabricated and divided in 3 groups: colorless, pigmented with makeup, and pigmented with iron oxide. Analysis of results was assessed on a Shore A hardness meter immediately, 6 months, and 1 year after fabrication of specimens, following the guidelines of the American Society for Testing and Materials. The hardness values were statistically analyzed by the Tukey test. The silicone exhibited an increase in hardness with time. However, the hardness was stable from 6 months to 1 year. It was concluded that the silicone is within the values of Shore A hardness reported in the literature, regardless of the storage period, pigmentation, and chemical disinfection.
Keywords: Maxillofacial prosthesis; silicones; disinfection; hardness